Green Stocks and Monetary Policy Shocks: Evidence from Europe - Michael D. Bauer; Eric A. Offner; Glenn D. Rudebusch (CESifo GmbH, 2024)
Policymakers and researchers worry that the low-carbon transition may be inadvertently delayed by higher global interest rates. To examine whether green investment is especially sensitive to interest rate increases, we consider the effect of unanticipated monetary policy changes on the equity prices of green and brown European firms. We find that brown firms, measured in terms of carbon emission levels or intensities, are more negatively affected than green firms by tighter monetary policy. This heterogeneity is robust to different monetary policy surprises, emission measures, econometric methods, and sample periods, and it is not explained by other firm characteristics. This evidence suggests that higher interest rates may not skew investment away from a sustainable transition.
Keywords: E52; G14; Q54; Q58; 330; monetary transmission; carbon premium; ESG; climate finance